2023
DOI: 10.3892/ol.2023.14024
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of nutritional and inflammatory markers in patients with hepatocellular carcinoma who receive immune checkpoint inhibitors

Chunxun Liu,
Haoran Zhao,
Rujia Zhang
et al.

Abstract: The emergence of immune checkpoint inhibitors (ICIs) has provided a new treatment option for patients with hepatocellular carcinoma (HCC). However, further evaluation is needed for determining biomarkers for the use of ICIs. The present study evaluated the prognostic value of certain nutritional and inflammatory markers in patients with HCC who received ICIs. In the present study, the clinical data of 151 patients with HCC who received ICIs at Harbin Medical University Cancer Hospital from January 2019 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Following the removal of duplicate studies and initial screening of titles and abstracts, we proceeded to evaluate the full texts of 22 articles. Among them, 15 articles with 19 studies met the eligibility criteria, resulting in a total of 3335 patients [ 19 , 22 , 29 41 ]. The study selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following the removal of duplicate studies and initial screening of titles and abstracts, we proceeded to evaluate the full texts of 22 articles. Among them, 15 articles with 19 studies met the eligibility criteria, resulting in a total of 3335 patients [ 19 , 22 , 29 41 ]. The study selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After analyzing data from 151 HCC patients, they found that these inflammatory and nutritional indicators possess certain prognostic value, particularly the nutritional biomarkers. In a prospective study on gastric cancer, Ding and his colleagues, through the analysis of data from 30 gastric cancer patients, identified that the combination of SII and PNI effectively predicts the outcome for gastric cancer patients receiving sintilimab [ 17 , 21 ]. However, these markers have been established and applied for an extended period.…”
Section: Introductionmentioning
confidence: 99%